Implementasi Sistem Pengelolaan Persediaan dengan Algoritma FIFO Pada Gudang Sparepart Sepeda Motor - Syahputra, Mhd. Dana Anggara; Santoso, Heri; Sibarani, Fathiya Hasyifah (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The role of Information Systems is crucial for company activities, particularly as a support for inventory management to enhance efficiency. Currently, manual activities in recording inventory result in data inaccuracies due to complex physical counting. By proposing the implementation of the Last-In, First-Out (LIFO) algorithm and using the waterfall system development method,, this study focuses on a solution to improve the speed and accuracy of inventory information. The LIFO algorithm is utilized to rectify recording inaccuracies by adhering to the principle of selling the most recently acquired items first. This implementation provides an effective solution to challenges in item issuance and facilitates quick and accurate access to inventory information. Thus, this research aims to enhance the inventory management system of the Motorcycle Spare Parts Warehouse, improve operational efficiency, and facilitate more effective inventory information needs.